The Effect of Information Systems on Employee Performance Moderated by Job Satisfaction and Competence at a Private Hospital in Medan - Lubis, Fajar Rezeki; Kolibu, Inri E; Romy, Elly; Faris, Salman; Guci, Dede Ansyari; Nainggolan, Tuty (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2026)
This study aims to examine the effect of information systems on employee performance with job satisfaction and competence as moderating variables in a private hospital in Medan. As hospitals increasingly rely on digital systems to handle administrative tasks, medical records, and internal communication, the ability of employees to adopt and utilize information systems becomes critical to organizational productivity. The research uses a quantitative approach with survey methods, involving employees from various hospital departments who use information systems in their daily work routines. Data were analyzed using statistical techniques to determine both direct and moderating effects. The results show that information systems have a significant positive influence on employee performance, indicating that system effectiveness contributes directly to better work outcomes. Job satisfaction is found to strengthen this relationship, highlighting that employees who feel motivated, valued, and comfortable with their work environment are more likely to maximize the use of information systems. Meanwhile, competence also acts as an effective moderator, suggesting that employees with higher levels of skill and digital literacy are better able to translate system usage into improved performance.